Analyzing Genetic Variability and Heritability of Yield Related Traits in Papaya (Carica papaya L.) via Line Tester Method - Veersain; Satya Prakash; Arvind Kumar; L.K. Gangwar; Vishal Gangwar; Mohit Kumar; Upendra Maurya; Avdhesh Kumar; Akanksha Marwah; Rupesh Kumar (The Bioscan, 2025)
This study evaluates the genetic variability, heritability, and correlation among 41 diverse papaya genotypes across 15 traits to identify potential avenues for crop enhancement. Significant variation was observed in traits such as plant height (ranging from 90.97 cm to 177.33 cm), flowering initiation (196.67 to 228 days), and flowering duration (210.27 to 235.33 days). High heritability values were noted for plant height at flowering (98.39%), fruit yield per plant (98.22%), and fruit length (95.26%), indicating these traits are predominantly influenced by genetic factors and are suitable targets for breeding programs. Genetic advance calculations showed substantial potential for improvement in traits like plant height at flowering (70.68%) and fruit yield per plant (62.69%). Correlation analyses revealed significant positive associations between fruit yield per plant and traits such as fruits per plant (0.8406) and plant height (0.612). These findings underscore the potential for effective selection and hybrid breeding programs to enhance papaya yield and quality. Negative significant effects were observed in certain crosses, suggesting the complexity of heterosis effects and the importance of selecting compatible parental lines. Overall, this research highlights the rich genetic variability in papaya and provides valuable insights for breeding programs aimed at improving crop yield and quality.